FAKTOR-FAKTOR YANG MEMPENGARUHI PINJAMAN MODAL PETANI IKAN MAS KE PT.BPR DIAN SINARTA DAN PERBANDINGAN PENDAPATAN ANTARA PEMINJAM DAN NON PEMINJAM MODAL - Romyanti, Romyanti; Sriyoto, Sriyoto; Reflis, Reflis (Jurnal AGRISEP, 2004)
A condition which is often find where farmers incapable to providing the capital because weakening of farmer fund which also result in weaken   source of farmer's own capital. The effect of this condition, farmers seldom have to use capital from outside both formal and informal sectors.   TIhis        research was objectived  to analyzing  factors influencing  the amount of goldfish farmer capital loan to PT.BPR DB in Desa  Tanjung Harapan Kecamatan  Padang Jaya Kabupaten  North Bengkulu  and compare the level earnings  of  goldfish  farmer  among of non capital lender and capital lender farmers to PT.BPR DB.  The result  showed that amount  dependent  of family responsibility,  goldfish  farming income and farmer  operating  cost  last season  have influenced  on level of the amount  of  goldfish  farmer capital loan, while as such as wide of fishpond, formal education level and farmers age do not have influence on. So, the difference of earnings  obtained  the average earnings compared to between bigger capital lender  to non capital lender.